EFFECTS OF VISCOUS DISSIPATION AND JOULE HEATING ON MHD FLOW OF A FLUID WITH VARIABLE PROPERTIES PAST ASTRETCHING VERTICAL PLATE - Khaled K. Jaber (European Scientific Journal, ESJ, 2014)
An analysis is presented to study the combined effects of viscous dissipation and Joule heating on MHD free-convective flow of a fluid with variable properties near a linearly stretching isothermal vertical sheet. The flow is subjected to a uniform transverse magnetic field, with high temperature differences between the plate and ambient fluid. The Boussinesq approximation is neglected due to the large temperature differences between the plate and the ambient fluid. The resulting coupled nonlinear differential equations are solved numerically. The effects of magnetic parameter, Grashof number,Eckert number and other involved parameters on the velocity and temperature functions are investigated.